Diagnostics of surface wave driven low pressure plasmas based on indium monoiodide-argon system. (27th May 2015) - Ögün, C M; Kaiser, C; Kling, R; Heering, W
Abstract: Indium monoiodide is proposed as a suitable alternative to hazardous mercury, i.e. the emitting component inside the compact fluorescent lamps (CFL), with comparable luminous efficacy. Indium monoiodide-argon low pressure lamps are electrodelessly driven with surface waves, which are launched and coupled into the lamp by the 'surfatron', a microwave coupler optimized for an efficient operation at a frequency of 2.45 GHz. A non intrusive diagnostic method based on spatially resolved optical emission spectroscopy is employed to characterize the plasma parameters. The line emission coefficients of the plasma are derived by means of Abel's inversion from the measured spectral radiance data. The characteristic plasma parameters, e.g. electron temperature and density are determined by comparing the experimentally obtained line emission coefficients with simulated ones from a collisional-radiative model. Additionally, a method to determine the absolute plasma efficiency via irradiance measurements without any goniometric setup is presented. In this way, the relationship between the plasma efficiency and the plasma parameters can be investigated systematically for different operating configurations, e.g. electrical input power, buffer gas pressure and cold spot temperature. The performance of indium monoiodide-argon plasma is compared with that of conventional CFLs.